Stabilization of Expansive Soil with Various Admixtures: A Brief Review - K. Murali; S. Ashok; N. Giridharan; K. Kaniyan Pandiarasan; P. Logesh (Novel Perspectives of Engineering Research Vol. 2, 2021)
The main objective of this paper is to critically review the admixtures for stabilization of expansive soil. Expansive soil or clayey soil which can change its volume when the water content is available i.e., swelling and shrinkage occurs. In urban areas, borrow earth is not easily available which has to be hauled from a long distance. Quite often, large areas are covered with highly plastic and expansive soil, which is not suitable for such purpose. It results on damage of building structures and road pavements due to its low strength and high expansion. The usage of admixtures can adversely improve the soil properties, thus stabilizing the clayey soil. Due to cationic exchange in lime stabilization, which lead to agglomeration and flocculation of soil, it causes significant effect in many properties of expansive soil such as plasticity index, compaction, swell potential, reduction of clay fraction and increase of silt and sand fraction.